Pilomyxoid Astrocytoma in Unusual Location in a Child with Neurofibromatosis Type 1: Case Report and Review of the Literature - Jiménez, Lincoln; Correa Rivas, María; Colón Castillo, Lillian; Rivera Zengotita, Marie; Colón, Gloria; Vigo, Juan; Mc Burney, Edward (Puerto Rico Health Sciences Journal, 2010)
Pilomyxoid astrocytoma (PMA) is a recently defined brain tumor believed to be a variant of pilocytic astrocytoma (PA ), but with a more aggressive course. Most PMAs occur in the optic-chiasmatic/hypothalamic (OC H) region but they have also been described in the posterior fossa, temporal lobe, and in the spinal cord. We report a girl with history of neurofibromatosis type 1 (NF-1) who presented with a PMA located in the left lateral ventricle. Despite the fact that most of PMAs occur in the hypothalamic region, high awareness should be given to lesions in unusual locations, thus expanding the current epidemiologically known locations for this tumor.